(untitled) (American Journal of Agricultural Science, Engineering, and Technology, 2024)
Intercropping, an essential cultivation pattern in modern agricultural systems, increases crop yields and soil quality. Pechay and spring onions are frequently intercropped to increase productivity per unit area. However, its management practice follows simple natural principles and its practice is limited only by the imagination of farmers. The objective of the study was to determine effective spatial arrangements for intercropping. The treatments tested were three intercropping ratios of peachy and spring onion in 1:1, 1:2, and 2:1 arrangements compared against the sole cropping. Land equivalent ratio (LER) was used to compare the land use efficiency of the intercrops with each sole crop and IBM SPSS software’s were used to compute the analysis of variance. The total yield of intercropped crops were greater than sole cropping, shown by LER>1. The overall advantage of intercropping ranged from 47% to 66%. The highest land equivalent value was recorded for 2:1 pechay and spring onion row arrangements indicated a yield advantage of 66% over sole crop. The partial land equivalent value of both crops in intercropping was less than one indicating the cohesiveness of both crops in intercropping. Thus, it can be concluded that 2 pechay: 1 spring onion intercropping is a viable agronomic option in increasing land use efficiency and increased food security. It is, therefore, imperative to demonstrate the best treatment under farmer’s condition.